(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Chronic obstructive pulmonary disease (COPD) is a widespread, slowly progressing condition of the respiratory system that is often regarded as a major source of morbidity and mortality. Despite being a chronic condition, COPD can experience severe exacerbations that cause coughing and shortness of breath. To reduce COPD-related mortality and morbidity, it is crucial to have knowledge of the diagnosis, proper oxygen titration, and effective therapy. Objective: To assess the Knowledge, Attitude and Practice level about management of Acute Exacerbation of COPD among EMS Professionals. Methodology: In India, the study included 120 emergency medical professionals. The study made use of a KAP questionnaire created by Sylvia Saade et al [2] that had already been tried and verified. After receiving the respondents’ informed consent, the questionnaire was conducted online. Discussion: The data analysis reveals that while EMS workers are knowledgeable of the aetiology, pathophysiology, and clinical characteristics of COPD, they still need further training in its management. Broad consensus was found among respondents about attitudes toward COPD, including the need for COPD patients to stop smoking and the role of passive smoking in the disease. However, there was disagreement among respondents regarding advice on exercising. Broad agreement was discovered among the respondents about COPD practises, specifically the use of and safety precautions for metered dosage inhalers (MDI). Conclusion: The study’s findings suggest that EMS professionals have a healthy level of knowledge, attitude, and practise regarding COPD. However, the results do highlight areas that need work, which might be the subject of subsequent training sessions. Despite having a small sample size, the study makes an effort to present a comprehensive picture of knowledge, attitudes, and practises related to COPD.